2022
DOI: 10.1108/pm-11-2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

Factors affect the housing prices in China: a systematic review of papers indexed in Chinese Science Citation Database

Abstract: PurposeThis paper aims to explore the factors that affect housing prices as per Chinese articles indexed in the Chinese Science Citation Database (CSCD). There were different foci regarding what drove housing prices in China in Chinese articles, and international journal articles in English. As most previous English articles only threw light on international research, it motivated the researchers to systematically review Chinese literature’s factors that affected housing prices in China.Design/methodology/appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…It might have excluded some of the latest studies published in other languages. As one of our research indicated that local language research might allow us to see other angles in housing price research (Li et al, Forthcoming 2022), similar research might be conducted to study prefabricated buildings. Detailed focus groups and surveys may be taken to see the professionals' perspectives on ESG and prefabricated buildings in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It might have excluded some of the latest studies published in other languages. As one of our research indicated that local language research might allow us to see other angles in housing price research (Li et al, Forthcoming 2022), similar research might be conducted to study prefabricated buildings. Detailed focus groups and surveys may be taken to see the professionals' perspectives on ESG and prefabricated buildings in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the African situation differs from those of other regions like Asia and with a centrally planned economy. As such the situation differs from some other countries like China where administration appeared as a special factor that affected the housing price above the economic, social, and environmental factors despite the planned economic system and direct government housing interventions including government investment and macro-control in the country (Li & Li, 2022).…”
Section: Review Of Related Literaturementioning
confidence: 79%
“…However, the African experience might not be similar to the situations in some other regions of developed and developing countries. For instance, N. Li and Li (2022) indicated that China in the Asia region has administration as a special factor affecting the housing situation above the other economic, social, and environmental factors.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations